2019
DOI: 10.1088/1361-648x/ab0fe4
|View full text |Cite
|
Sign up to set email alerts
|

Towards magnetic alumina: uncovering the roles of transition metal doping and electron hybridization in spin delocalization

Abstract: Judicious doping of normally diamagnetic alumina (Al2O3) could lead to bulk magnetism that would enable the usage of cutting edge technology, such as magnetoforming, to create advanced systems that take advantage of the high chemical and physical resilience of alumina. This study builds upon initial results (Nykwest et al 2018 J. Phys.: Condens. Matter 30 395801) which have shown that alumina doped with magnetic elements such as Fe and Ni should exhibit heightened magnetic activity. Here we expand the analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
11
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 29 publications
4
11
0
Order By: Relevance
“…2 . The trend is in agreement with our past work on bulk doped alumina 13 , with scandium and titanium being the most energetically favorable dopants introduced to the system overall, and nickel and copper the least favorable dopants for each respective aluminum substitutional site. This can be explained by the preference of Sc ([Ar]3d 4s ) and Ti ([Ar]3d 4s ) to donate 3 electrons to the octahedrally coordinated oxygen atoms, bringing their valency closer to Ar than the other considered dopants.…”
supporting
confidence: 91%
See 4 more Smart Citations
“…2 . The trend is in agreement with our past work on bulk doped alumina 13 , with scandium and titanium being the most energetically favorable dopants introduced to the system overall, and nickel and copper the least favorable dopants for each respective aluminum substitutional site. This can be explained by the preference of Sc ([Ar]3d 4s ) and Ti ([Ar]3d 4s ) to donate 3 electrons to the octahedrally coordinated oxygen atoms, bringing their valency closer to Ar than the other considered dopants.…”
supporting
confidence: 91%
“…It has been demonstrated that substituting a transition metal dopant could produce alumina that possesses both unpaired electrons and a net magnetic moment 12 . In addition, it was also determined that the delocalization of these unpaired electrons varied greatly between dopants 13 , which may affect the final magnetic properties of the doped system 14 . Previous work in metallic systems 15 17 has pointed toward enhanced magnetism near surfaces, where a transition in spin density from the bulk to the surface region was observed.…”
mentioning
confidence: 99%
See 3 more Smart Citations